2021
DOI: 10.1038/s41598-021-90932-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of transcriptional responses of Dectes texanus LeConte (Coleoptera: Cerambycidae) larvae fed on three different host plants and artificial diet

Abstract: Dectes texanus is an important coleopteran pest of soybeans and cultivated sunflowers in the Midwestern United States that causes yield losses by girdling stems of their host plants. Although sunflower and giant ragweed are primary hosts of D. texanus, they began colonizing soybeans approximately 50 years ago and no reliable management method has been established to prevent or reduce losses by this pest. To identify genes putatively involved when feeding soybean, we compared gene expression of D. texanus third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 141 publications
0
7
1
Order By: Relevance
“…The study of insects and symbiotic intestinal microbes provides a basis for subsequent functional studies. 17,[20][21][22][23][24][25][26][27][28][29][30][31][32] The gut microbiome can be influenced by external environmental factors such as weather, temperature, and other factors such as antibiotics. [33][34][35] There were significant differences in microbial communities at different developmental stages of insects such as G. molesta, Heliothis virescens, Nilaparvata lugens and Zeugodacus tau.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of insects and symbiotic intestinal microbes provides a basis for subsequent functional studies. 17,[20][21][22][23][24][25][26][27][28][29][30][31][32] The gut microbiome can be influenced by external environmental factors such as weather, temperature, and other factors such as antibiotics. [33][34][35] There were significant differences in microbial communities at different developmental stages of insects such as G. molesta, Heliothis virescens, Nilaparvata lugens and Zeugodacus tau.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted in bees and termites in Hymenoptera, fruit flies and mosquitoes in Diptera, Dectes texanus in Coleoptera, and in the Lepidopteran pests Grapholita molesta , Carposina sasakii , Cydia pomonella , Spodoptera litura , Lymantria dispar , Manduca sexta , Helicoverpa armigera , Plutella xylostella and S. frugiperda . The study of insects and symbiotic intestinal microbes provides a basis for subsequent functional studies 17,20–32 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more insect microbial communities have been discovered and studied. Studies have been reported in honeybees [34][35][36][37], fruit flies [38][39][40], mosquitoes [41,42], Dectes texanus [43], and termites [44,45], as well as in lepidopteran pests, such as Grapholita molesta [18,[46][47][48], Carposina sasakii [46,47], and Cydia pomonella [47]. The gut microbial community of the honeybee has stable species and structure, and there are many unique microbial types in different regions of Apis mellifera.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible changes in the gut microbial community may be due to diverse feeding [49]. Compared with D. texanus fed on different hosts, 514 unigenes were differentially expressed in larvae feeding on soybeans [43]. Host specificity in biodiversity highlights the different degrees and interactive diversity across the levels of biodiversity in the system.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, detoxification was not among the overrepresented GO terms associated with transcripts upregulated following 12-h exposures to maize compared to other plant exposures, in contrast to predictions in other insect species [15,[124][125][126][127][128]. Regardless, 50 P450s were predicted with a majority being up-regulated (78%) or putatively belonging to clan CYP6.…”
Section: Discussionmentioning
confidence: 69%